PENERAPAN STRATEGI PEMBELAJARAN KONTEKSTUAL BERBASIS GAYA BELAJAR VAK (VISUAL, AUDITORI, KINESTETIK) TERHADAPA PENCAPAIAN KOMPETENSI SISWA KELAS VII SMP NEGERI 34 PADANG - Wahda Salamah; Mahrizal Mahrizal; Ramli Ramli (PILLAR OF PHYSICS EDUCATION, 2016)
Every student has learning styles for receive information, but it tend at one of learning styles. The teacher should be using the student’s learning style with learning strategies. The background of this research is lack of implementation of learning strategies. The solution to solve this problem is to implement contextual learning strategy based VAK learning styles (Visual, Auditory, Kinesthetic). The population of this research is all students in grade VII at SMPN 34 Padang of academic year 2015/2016. The sample of this research use purposive sampling. Data of this reseach is the competence of science students as competence attitudes, knowledge and skill. The instrument this research is written test, observation sheet and performance assessment sheet. Data analysis on the competense of khowledge, spiritual, social and skill use equality test two averages with t’ is 3,8186; 2,224; 3,3987; 3,316 while for ttable is  2,0792; 6,575; 5,0372; 1,593. based on the hypothesis is concluded that there are significant means the implementation of contextual learning strategy based VAK learning styles (Visual, Auditory, Kinesthetic) on achievement of the knowledge and skills competence of students in grade VII at SMPN 34 Padang and there is no influence means the implementation of contextual learning strategy based VAK learning styles (Visual, Auditory, Kinesthetic) on achievement of the spiritual and skill competence of students in grade VII at SMPN 34 Padang